Optimalisasi Kinerja Karyawan melalui Program Pelatihan di PT Indosat Tbk, Gerai Jakarta Pusat - Suntari, Esti; Utomo, Styo Budi; Tumanggor, Rahmayanti (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
This research aims to find out how much influence training has on employee performance, and the object of this research is employees at PT. Indosat Tbk. Hypothesis testing is to determine the significance of the influence between the Training variable and the Employee Performance variable. The research method used is quantitative descriptive research in which research data uses numbers to conclude the results of research conducted by PT. Indosat Tbk To determine whether or not there is an influence of training on employee performance, the data collection method in this research is a questionnaire. The population was 74 employees using the saturated sampling method. Based on the analysis results, it was found that employee training at PT. Indosat Tbk is well-received, with a significant majority of respondents expressing satisfaction ("Strongly Agree" and "Agree" responses totaling 80.13%). This indicates that employees actively participate in training and consistently apply the knowledge gained. Additionally, the performance of employees also garnered positive feedback, with a majority indicating strong performance ("Strongly Agree" and "Agree" responses totaling 77.11%). A determinant coefficient of 29.16% suggests that training contributes significantly to employee performance, while other factors not considered in the training program account for the remaining influence. Furthermore, statistical testing confirmed that training has a significant impact on employee performance, as evidenced by the rejection of the null hypothesis.